Micromachining - Cook, Jerome T.; Tolinski, Michael; Society of Manufacturing Engineers ([Dearborn, MI] : Society of Manufacturing Engineers, 2005)
Using animation and footage from clean-room production facilities, this program presents case studies of companies and research institutions using various micromachining methods
Title from title screen
Executive producer, Steven R. Bollinger
Keywords: Micromachining; Micromecanizado